Fungsi Dewan Perwakilan Daerah dalam Perencanaan dan Pengawasan terhadap Pengelolaan Keuangan Negara (APBN) - Fazky Muhammad Hasa; Efik Yusdiansyah; Fabian Fadhly Jambak (UNISBA Press, 2022)
Abstract. The DPD has the authority to submit draft laws to the DPR, participate in discussing draft laws and provide considerations to the DPR on the APBN Bill. The word